KEGIATAN BIMBINGAN BELAJAR SIGMA DALAM MENGATASI MINAT BELAJAR SISWA - Listiani, Tanti; Saragih, Melda Jaya; Appulembang, Oce Datu Appulembang; Indriani, Siane; Widiastuti, Widiastuti (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Many students experience obstacles during online learning. One is a lack of interest in learning materials. Students feel bored because they have to stare at a computer screen. The problem of low interest in learning is certainly serious because it can result in low student learning outcomes and learning goals not being achieved optimally. For this reason, students need to be given extra assistance so that their interest in learning can improves again. Therefore, tutoring is needed that can help students with learning difficulties. Sigma tutoring is tutoring that has existed for approximately two years. Now, Sigma Tutoring will continue its vision to guide students in facing learning difficulties. Sigma Tutoring provides free tutoring services for residents, especially children from primary to high school level. This tutoring was held in Perumnas Tangerang with around 20 students and nine tutors. To see the impact of this tutoring, it will be described qualitatively through a distributed questionnaire. As a result, through Sigma's tutoring, students who took lessons had a high interest in learning with an average of 76.23%. Hopefully, Sigma Tutoring can continue to be a blessing for students and tutors can practice their teaching skills.